Icast 2007 Advancement through technology & education (2007)
The moduli of elasticity and rupture, and the energy to cause failure under impact load of oil palm truck were determined. Samples for testing were obtained from the base, middle and top of the tree truck. They were taken from both the core and outer region of the truck and tested wet and dry conditions. the samples obtained from the outer layer of the base and tested under wet and dry conditions, gave the highest modulus of elasticity of 4943 N/mm and a modulus of ruture of 42.8 N/mm. The samples obtained from the inner section of the top and tested under wet condition gave the lowest values of 369.7 N/mm for modulusof elasticity and 0.4 N/mm for modulus of rupture. The maximum value of energy consumption of 12.86 joules was recorded for the samples from the inner portion of the top and tested under dry condition. There was a general decrease from the base to the top for the three parameters and from inside to the outer section.